Diagnostics of RT-PCR Accuracy and GeneXpert Method on Covid-19 Examination - Seprina Zulaini (Majalah Kedokteran Andalas, 2023)
The COVID-19 pandemic raises demands for significant diagnostics at all pre-analytical and post-analytical levels. At the beginning of the pandemic, molecular diagnostic tests were still limited and tended to take a long time. So far, the cases examined were using the Real-Time Polymerase Chain Reaction (RT-PCR) method. This method can be run on multiple samples and has a turnaround time of fewer than 4 hours. This study compared the accuracy of RT-PCR and GeneXpert Xpress assays in the Covid-19 test. This study examined 30 samples of suspected Covid-19 patients collected at the Central Laboratory of Diagnostic and Infectious Diseases Research, Andalas University, and the Laboratory of the West Sumatra Lung Hospital. The examination was carried out using the RT-PCR method and then GeneXpert with a cut-off value of 37.5 and 42.5, respectively. The results showed that the examination using GeneXpert had a sensitivity value of 96%, specificity of 100%, positive and negative predictive values of 100% and 83%, and accuracy of 480%. This proves that testing using GeneXpert has a high level of accuracy and can be used as a reliable alternative in diagnosing Covid-19 samples.